1988
DOI: 10.1111/j.1365-3083.1988.tb02430.x
|View full text |Cite
|
Sign up to set email alerts
|

Human T Lymphocyte Differentiation Antigens as Target for Immunotoxins or Complement‐Mediated Cytotoxicity

Abstract: Graft-versus-host disease (GVHD) after allogeneic bone marrow transplantation (BMT) is initiated by immunocompetent T cells present in the graft. Selective elimination of distinct T-cell subsets or a sufficient, but not complete T-cell depletion, might abolish severe GVHD without graft rejection and loss of the anti-tumour potential. In this study we analysed the efficacy of different monoclonal antibodies (MoAb) WT32 (CD3), OKT4 (CD4), T101 (CD5), WT1 (CD7), and WT82 (CD8) with respect to their cytotoxicity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Similarly, a ricin A chain immunotoxin against the L3T4 antigen inhibited the ability of lymph hode cells from primed mice to induce antigen-specific B cells to proliferate and secrete IgM in vitro with an ICs0 ~> 1 nM [16]. Recently, Preijers et al reported that ricin A chain linked to the OKT4 antibody against the human CD4 antigen showed only low toxicity to human peripheral blood lymphocytes in vitro [13]. We have also found that a ricin A chain immunotoxin made with the monoclonal antibody M-T310, which binds to an epitope on the CD4 antigen distinct from that recognised by M-T151 [15], was also weakly toxic to the CEM cell line with an IC50 >5 nM (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a ricin A chain immunotoxin against the L3T4 antigen inhibited the ability of lymph hode cells from primed mice to induce antigen-specific B cells to proliferate and secrete IgM in vitro with an ICs0 ~> 1 nM [16]. Recently, Preijers et al reported that ricin A chain linked to the OKT4 antibody against the human CD4 antigen showed only low toxicity to human peripheral blood lymphocytes in vitro [13]. We have also found that a ricin A chain immunotoxin made with the monoclonal antibody M-T310, which binds to an epitope on the CD4 antigen distinct from that recognised by M-T151 [15], was also weakly toxic to the CEM cell line with an IC50 >5 nM (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…MoAb-RTA and MoAb-Gel conjugates are also Correspondence: Dr Dianne Fishwild, GenPharm Intemational, 297 North Bernardo Avenue, Mountain View, CA 94043, LTSA. cytotoxic for murine and human lymphoid cells in vitro [3,7,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…When PBMC from one donor were tested on three separate occasions, a reproducible susceptibility pattern emerged with the rGelc247 and RTA30 conjugates. Specifically, the median IC50 values (range) for H65-RTA30, cH65-rGelc247, cH65 F(ab')2-rGelc247 and cH65 Fab'-rGelc247 were 300 pM RIP (240-410), 54 (51-78), 25 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) and 59 (59-61), respectively. Furthermore, the relative potencies of the immunoconjugates were the same as when PBMC from multiple donors were tested.…”
Section: Gel Conjugates Are More Potent Than Rta^q Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation